Indels markers set and ancestry estimates in a population sample from Atlantic Department of Colombia. (December 2015) - Garavito, G.; Martinez, B.; Builes, J.J.; Aguirre, D.; Mendoza, L.; Afanador, C.H.; Egea, E.; Marrugo, J.
Abstract: Ancestry Informative Markers InDels (AIM-InDels) show high allele frequency variation between ancestral populations and are useful to estimate individual and population ancestry. Our goal was to characterize the frequencies of 46 AIM-InDels in a population sample of 50 individuals from Barranquilla city, Atlantic Department in Colombia. The ancestral components were calculated according to the methodology described in [1]; using STRUCTURE v2.3.3 with a burnin length of 100, 000 followed by 100, 000 MCMC, with a K  = 3, considering the "Admixture Model" and correlated allele frequencies. As parental populations, the genetic profiles of 322 individuals (Africans: 105 Europeans: 158, Native Americans: 59) [1] and 42 Native American individuals[8] were used. The contribution of each founder population was estimated in: 24.7% of African, 27.6% of Native American and 47.7% of European. These findings reveal different admixture histories of the studied population, and generate reliable ancestry estimates useful to investigate association between ancestry and genetic complex disorders.